Sociabilidad y Fraternidad. Influencias masónicas en la creación de círculos asociativos (1800-1850) - Zozaya-Montes, Maria (2013)
In 1800 freemasonry was quite widespread in Europe and also in Spain. It was a secret movement prosecuted by the absolutism. It was strongly linked with those principles of Liberalism, and those of the French Revolution: liberty, equality and fraternity. The so-called “spirit of sociability” was quite related with that of fraternity, which was an essential element for the freemasonry. In my opinion, the masonic ideas of fraternity and the structure supporting the union and friendship on their organizations were copied by the new casinos, clubs and athenaeums. Those were the new associations created in Spain since the 1830´s, which born with the Liberalism. As is shown here, related with the freemasonry, those circles promoted those ideas of fraternity by different ways. Firstly in their iconography: stamps, tokens and other symbols in different materials. Secondly: the principles written on their texts. Thirdly: their own normative structure, including the rhetorical norms in statutes, and also the real rules in quotidian life.